Role of Non-coding RNAs in the Pathogenesis of Endometriosis - Ghafouri-Fard, Soudeh; Shoorei, Hamed; Taheri, Mohammad (Frontiers in Oncology, 2020)
Endometriosis is a disorder characterized by the presence of endometrial glands and stroma like lesions outside of the uterus. Although several hypothesis have tried to explain the underlying cause of endometriosis, yet the main cause remained obscure. Recent studies have shown contribution of non-coding RNAs in the pathogenesis of endometriosis. Two classes of these transcripts namely long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) have mostly attracted attention of researchers. Several studies have reported aberrant expression of these transcripts in affected tissues from patients as well as animal models. Modulation of important signaling pathways such as PI3K/AKT, P38-MAPK, ERK1/2-MAPK and Wnt-β catenin by miRNAs and lncRNAs have potentiated these molecules as biomarkers or therapeutic agents in endometriosis. Single nucleotide polymorphisms with miR-126, miR-143 and miR-146b have been associated with risk of endometriosis. Moreover, miRNAs and lncRNAs control inflammatory responses, cell proliferation, angiogenesis and tissue remodeling, thus understanding the role of these transcripts in endometriosis is a possible way to develop novel diagnostic tests and therapeutic targets for this disorder.